Solvent-free synthesis of novel para-menthane-3,8-diol ester derivatives from citronellal using a polymer-supported scandium triflate catalyst - Mafu, Lubabalo; Zeelie, Ben; Watts, Paul (Beilstein Journal of Organic Chemistry, 2016)
The use of natural resources as a chemical feedstock for the synthesis of added-value products is gaining interest; as such we report an environmentally friendly method for the synthesis of para-menthane-3,8-diol from natural citronellal oil in 96% yield, under solvent free aqueous conditions. The acylation of para-menthane-3,8-diol with various acid anhydrides over polymer-supported scandium triflate (PS-Sc(OTf)3) catalyst was subsequently developed, where both hydroxy groups of para-menthane-3,8-diol could be simultaneous acylated under mild reaction conditions to form the corresponding diesters in good yields. The advantages of this method include a simple procedure from natural resources, using solvent-free reaction conditions.
Keywords: acylation; diesters; para-menthane-3,8-diol; PS-Sc(OTf)3

(untitled) - da Silva, K. A.; Robles-Dutenhefner, P. A.; Sousa, E. M. B.; Kozhevnikova, E. F.; Kozhevnikov, I. V.; Gusevskaya, E. V. (Catal. Commun., 2004)

(untitled) - Drapeau, J.; Rossano, M.; Touraud, D.; Obermayr, U.; Geier, M.; Rose, A.; Kunz, W. (C. R. Chim., 2011)

(untitled) - Imachi, S.; Owada, K.; Onaka, M. (J. Mol. Catal. A: Chem., 2007)

(untitled) - Nie, Y.; Niah, W.; Jaenicke, S.; Chuah, G.-K. (J. Catal., 2007)

(untitled) - Heravi, M. M.; Behbahani, F. K.; Bamoharram, F. F. (ARKIVOC, 2007)

(untitled) - Sharma, R. K.; Gulati, S. (J. Mol. Catal. A: Chem., 2012)

(untitled) - Chandra, K. L.; Saravanan, P.; Singh, R. K.; Singh, V. K. (Tetrahedron, 2002)

(untitled) - Pârvulescu, A. N.; Gagea, B. C.; Poncelet, G.; Pârvulescu, V. I. (Appl. Catal., A, 2006)

(untitled) - Tashiro, D.; Kawasaki, Y.; Sakaguchi, S.; Ishii, Y. (J. Org. Chem., 1997)

(untitled) - Dumeunier, R.; Markó, I. E. (Tetrahedron Lett., 2004)

Synthesis of p-menthane-3,8-diol - Mpuhlu, B. (2007)

(untitled) - Firouzabadi, H.; Iranpoor, N.; Farahi, S. (J. Mol. Catal. A: Chem., 2008)